1972
DOI: 10.1172/jci107134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Chronic Renal Insufficiency on Bone Mineral and Collagen Maturation

Abstract: A B S T R A C T The effect of chronic renal disease on bone matrix and mineral maturation was evaluated in rats with experimental renal insufficiency of 2-11 wk duration utilizing bromoform-toluene gradient fractionation of bone powder, pulse labeling experiments with "5Ca and proline-'H differential extraction, an(d X-ray diffraction techniques.Maturation defects in both collagen and minieral (45Ca) metabolism were documented as early as 2 wk after the induction of uremia, when total bone calcium, inorganic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

1973
1973
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 47 publications
2
34
1
Order By: Relevance
“…Previous investigations have been concerned primarily with rates of bone mineral (apatite) and matrix (collagen) turnover, under the assumption that the intricate processes of crystal growth and collagen maturation were proceeding in normal fashion. In an earlier study, we demonstrated maturational alterations in bone collagen and mineral metabolism in the experimental uremic state that progressed with advancing uremia, although insignificant alterations in plasma pH, calcium, and bone carbonate content obtained (3). The present study was undertaken to determine whether the apparent collagen maturational defect in the advancing uremic state is associated with compositional and structural alterations of the mineral components of skeletal tissue.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous investigations have been concerned primarily with rates of bone mineral (apatite) and matrix (collagen) turnover, under the assumption that the intricate processes of crystal growth and collagen maturation were proceeding in normal fashion. In an earlier study, we demonstrated maturational alterations in bone collagen and mineral metabolism in the experimental uremic state that progressed with advancing uremia, although insignificant alterations in plasma pH, calcium, and bone carbonate content obtained (3). The present study was undertaken to determine whether the apparent collagen maturational defect in the advancing uremic state is associated with compositional and structural alterations of the mineral components of skeletal tissue.…”
Section: Introductionmentioning
confidence: 75%
“…Female Holtzman rats at 6 wk of age were unilaterally nephrectomized with contralateral segmental renal infarction, resulting in an impairment of 7/8 normal kidney function as previously described (3). This ischemic infarction of functioning renal mass persisted during the subsequent 2, 5, or 9-wk period of study.…”
Section: Methodsmentioning
confidence: 99%
“…Magnesium has been shown to stabilize certain amorphous calcium-phosphate deposits and to prevent crystal formation (19). In turn Russell and Avioli have shown that immature bone is increased in uremic rats (20), which could be a consequence of the increased magnesium content. The fact that high magnesium bones required greater heat to induce crystal enlargement further suggests that magnesium may stabilize and determine crystal size in uremic bone.…”
Section: Cortical and Trabecular Bone Magnesiummentioning
confidence: 99%
“…Chronically uremic rats were produced surgically by unilateral nephrectomy and segmental infarction of the contralateral kidney after ligation of two of the renal arterial branches (26). Supplemental …”
Section: Introductionmentioning
confidence: 99%